Accountability of Nazir in the Waqf Legal System of Indonesia - Ahmad 'Azam bin Mohd Sharif; Nasrullah Nasrullah; Muhammad Hatta; Hidayatullah Hidayatullah (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Good waqf management will provide benefits and contribute to developing the people's economy and alleviating poverty. Nazir greatly influences this in his responsibilities as the manager of waqf assets. This study aims to provide an analysis of Nazir's responsibilities as the manager of waqf assets according to the waqf legal system in Indonesia and an overview of how to revitalize Nazir's status, roles and responsibilities in managing waqf in Indonesia. This research is normative legal research with a statutory regulation approach. The results of this research are that according to Waqf law in Indonesia, Nazir's responsibility in carrying out his roles, duties, functions and authority is one of the things that Nazir bears. Mistakes made by Nazir in managing waqf will have an impact on problems of administrative sanctions and even criminal. However, along with the weight of Nazir's responsibility, it has yet to be accompanied by the Indonesian waqf legal system favouring Nazir. One way to revitalize Nazir's status, roles and responsibilities are by revising or reconstructing the Law on Nazir in waqf law in Indonesia to include nazir in one of the pillars of waqf.